Increased susceptibility of spontaneously hypertensive rats to ventricular tachyarrhythmias in early hypertension. (18th January 2016) - Nguyen, Thao P.; Sovari, Ali A.; Pezhouman, Arash; Iyer, Shankar; Cao, Hong; Ko, Christopher Y.; Bapat, Aneesh; Vahdani, Nooshin; Ghanim, Mostafa; Fishbein, Michael C.; Karagueuzian, Hrayr S.
Abstract : Key points: Hypertension is a risk factor for sudden cardiac death caused by ventricular tachycardia and fibrillation. Whether hypertension in its early stage is associated with an increased risk of ventricular tachyarrhythmias is not known. Based on experiments performed at the cellular and whole heart levels, we show that, even early in chronic hypertension, the hypertrophied and fibrotic ventricles of spontaneously hypertensive rats aged 5 to 6 months have already developed increased stress‐induced arrhythmogenicity, and this increased susceptibility to ventricular arrhythmias is primarily a result of tissue remodelling rather than cellular electrophysiological changes. Our findings highlight the need for early hypertension treatment to minimize myocardial fibrosis, ventricular hypertrophy, and arrhythmias. Abstract: Hypertension is a risk factor for sudden cardiac death caused by ventricular tachycardia and fibrillation (VT/VF). We hypothesized that, in early hypertension, the susceptibility to stress‐induced VT/VF increases. We compared the susceptibility of 5‐ to 6‐month‐old male spontaneously hypertensive rats (SHR) and age/sex‐matched normotensive rats (NR) to VT/VF during challenge with oxidative stress (H2 O2 ; 0.15 mmol l −1 ). We found that only SHR hearts exhibited left ventricular fibrosis and hypertrophy. H2 O2 promoted VT in all 30 SHR but none of the NR hearts. In 33% of SHR cases, focal VT degenerated to VF within 3 s. Simultaneous voltage‐calcium optical mapping of Langendorff‐perfused SHR hearts revealed that H2 O2 ‐induced VT/VF arose spontaneously from focal activations at the base and mid left ventricular epicardium. Microelectrode recording of SHR hearts showed that VT was initiated by early afterdepolarization (EAD)‐mediated triggered activity. However, despite the increased susceptibility of SHR hearts to VT/VF, patch clamped isolated SHR ventricular myocytes developed EADs and triggered activity to the same extent as NR ventricular myocytes, except with larger EAD amplitude. During the early stages of hypertension, when challenged with oxidative stress, SHR hearts showed an increased ventricular arrhythmogenicity that stems primarily from tissue remodelling (hypertrophy, fibrosis) rather than cellular electrophysiological changes. Our findings highlight the need for early hypertension treatment to minimize myocardial fibrosis, ventricular hypertrophy, and arrhythmias. Key points: Hypertension is a risk factor for sudden cardiac death caused by ventricular tachycardia and fibrillation. Whether hypertension in its early stage is associated with an increased risk of ventricular tachyarrhythmias is not known. Based on experiments performed at the cellular and whole heart levels, we show that, even early in chronic hypertension, the hypertrophied and fibrotic ventricles of spontaneously hypertensive rats aged 5 to 6 months have already developed increased stress‐induced arrhythmogenicity, and this increased susceptibility to ventricular arrhythmias is primarily a result of tissue remodelling rather than cellular electrophysiological changes. Our findings highlight the need for early hypertension treatment to minimize myocardial fibrosis, ventricular hypertrophy, and arrhythmias.